Exploring Agrarian Reform Laws in Indonesia - Krismantoro, Damianus (Journal of Ecohumanism, 2024)
Agrarian reform serves as a crucial mechanism for reorganizing land control, ownership, utilization, and addressing agrarian disputes and conflicts, ultimately aiming to achieve justice and enhance the welfare of the people. In Indonesia, the legal framework for agrarian reform is established by the Basic Agrarian Law, formally known as Number 5 of 1960. Nevertheless, the practical implementation of agrarian reform has proven to be a challenging endeavor, often falling short of expectations. This research employs a normative juridical approach, which examines existing and historical laws, as well as potential future legislation. This approach is complemented by statutory, conceptual, historical, and comparative analyses. The findings of this study reveal that the resolution of agrarian conflicts across various regions and provinces in Indonesia has not shown significant improvement over time. Despite ongoing efforts to address agrarian conflicts, there has been a perceived lack of substantial change in the outcomes. These findings underscore the complexity and persistent challenges associated with agrarian reform in Indonesia. Addressing the issues related to land control, ownership, and disputes requires a multifaceted approach that goes beyond legislation, necessitating a closer examination of the root causes and more effective strategies for implementation.